PENGGUNAAN MODEL E-S-QUAL DALAM STUDI PENGARUH KUALITAS LAYANAN PERBANKAN ONLINE TERHADAP KEPUASAN NASABAH - Tatik Suryani; May Sumiati (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2010)
There are many models for measuring service quality, SERVQUAL, SERPERF, STIEQUAL,E-SQ and E-S-QUAL. Every model offers some advantages and weakness. Previous researchproved that E-S-QUAL model is the best assessment to measure online service qualityin banking industry because it has an excellent external validity and enough consistency inreliability. The objectives of this research are to examine the effects of online service qualityin banking industry on the effect on customer satisfaction. Research involved 124 customersinternet banking. By measuring criterion validity of E-S-QUAL, it found that E-S-QUAL has agood validity and reliability for measuring the quality of banking online services. By using Ftest, the result revealed that all dimensions of online service quality has significantly effectson customer satisfaction. By using t –test only site aesthetic variable has significantly effecton customer satisfaction. The managerial implication of this research is that banking industryshould develop online service not only for effeciency, system availability, privacy, assurance,but the most important thing is also the aesthetics aspect to enhance their customer satisfaction.Keywords : Customer Satisfaction, SERVQUAL, E-SQ, E-S-QUAL